Facing crisis - Gerevini, Stefania. (Washington, D.C.)
xii, 240 sayfa
Keywords: “Though Venice emerged as a leading Mediterranean power in the Trecento, the city faced a series of crises during a brief but cataclysmic period coinciding with Andrea Dandolo's dogeship (1343-1354): earthquakes, disease, fierce military conflicts, and dramatic political and institutional tensions had the republic on edge. It was nevertheless precisely at this time that the government sponsored the ambitious and sumptuous artistic campaigns in San Marco that are at the heart of this book: a reliquary-chapel, a new baptistery, and a folding altarpiece, all masterpieces crafted with unparalleled technical skill, blending Byzantine and Italianate visual forms. Far from being mere artistic commissions, these works were affirmative political interventions that interrogated the meaning of community, authority, and (shared) political leadership at a time when those notions were unsettled. Looking beyond established concepts of triumph and imperialism, this book situates the artistic interactions between Byzantium and Venice into ongoing processes of state formation and attests to the power of images to inform (and transform) political imaginations in troubled times. This study thus offers new insights into how medieval communities across the Mediterranean understood and responded to uncertainty through the visual, and in doing so, probes the value of “crisis“ as a methodological framework“--